The RUNX1b Isoform Defines Hemogenic Competency in Developing Human Endothelial Cells - Menegatti, Sara; Potts, Bethany; Garcia-Alegria, Eva; Paredes, Roberto; Lie-A-Ling, Michael; Lacaud, Georges; Kouskoff, Valerie (Frontiers in Cell and Developmental Biology, 2021)
The transcription factor RUNX1 is a master regulator of blood cell specification. During embryogenesis, hematopoietic progenitors are initially generated from hemogenic endothelium through an endothelium-to-hematopoietic transition controlled by RUNX1. Several studies have dissected the expression pattern and role of RUNX1 isoforms at the onset of mouse hematopoiesis, however, the precise pattern of RUNX1 isoform expression and biological output of RUNX1-expressing cells at the onset of human hematopoiesis is still not fully understood. Here, we investigated these questions using a RUNX1b::VENUS RUNX1c::TOMATO human embryonic stem cell line which allows multi-parameter single cell resolution via flow cytometry and isolation of RUNX1b-expressing cells for further analysis. Our data reveal the sequential expression of the two RUNX1 isoforms with RUNX1b expressed first in a subset of endothelial cells and during the endothelial to hematopoietic transition while RUNX1c only becomes expressed in fully specified blood cells. Furthermore, our data show that RUNX1b marks endothelial cells endowed with hemogenic potential and that RUNX1b expression level determines hemogenic competency in a dose-dependent manner. Together our data reveal the dynamic of RUNX1 isoforms expression at the onset of human blood specification and establish RUNX1b isoform as the earliest known marker for hemogenic competency.